Performance of End Milling Process on Advanced Ceramics - Moola, Mohan Reddy (Curtin University, 2012)
Experimental study has been carried out to investigate the performance of conventional CNC end milling machining technology with particular reference to Machinable Glass Ceramic and Aluminum Nitride Ceramic using three different cutting tools. The surface finish, tool life and cutting force have been chosen as measurements for machinability. Predictive mathematical models are developed and finally optimal machining parameters are determined in order to achieve good surface finish, high material removal rate and low cutting forces.